Involvement of gap junction channels in the pathophysiology of migraine with aura - Sarrouilhe, Denis; dejean, catherine; Mesnil, Marc (Frontiers in Physiology, 2014)
Migraine is a common, recurrent and disabling primary headache disorder with a genetic component which affects up to 20 % of the population. One third of all patients with migraine experiences aura, a focal neurological disturbance that manifests itself as visual, sensitive or motor symptoms preceding the headache. In the pathophysiology of migraine with aura, activation of the trigeminovascular system from the meningeal vessels mediates migraine pain via the brainstem and projections ascend to the thalamus and cortex. Cortical spreading depression (CSD) was proposed to trigger migraine aura and to activate perivascular trigeminal nerves in the cortex. Quinine, quinidine and the derivative mefloquine are able to inhibit CSD suggesting an involvement of neuronal connexin36 channels in CSD propagation. More recently, CSD was shown to induce headache by activating the trigeminovascular system through the opening of stressed neuronal Pannexin1 channels. A novel benzopyran compound, tonabersat, was selected for clinical trial on the basis of its inhibitory activity on CSD and neurogenic inflammation in animal models of migraine. Interestingly, in the time course of animal model trials, tonabersat was shown to inhibit trigeminal ganglion neuronal-glial cell gap junctions, suggesting that this compound could prevent peripheral sensitization within the ganglion. Three clinical trials aimed at investigating the effectiveness of tonabersat as a preventive drug were negative, and conflicting results were obtained in other trials concerning its ability to relieve attacks. In contrast, in another clinical trial, tonabersat showed a preventive effect on attacks of migraine with aura but had no efficacy on non-aura attacks. Gap junction channels seem to be involved in several ways in the pathophysiology of migraine with aura and emerge as a new promising putative target in treatment of this disorder.